2018
DOI: 10.2196/10297
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Genetic Data Across Individuals: Design and Evaluation of a Novel Comparative Report Tool

Abstract: BackgroundThe growth in the availability of personal genomic data to nonexperts poses multiple challenges to human-computer interaction research; data are highly sensitive, complex, and have health implications for individuals and families. However, there has been little research on how nonexpert users explore their genomic data.ObjectiveWe focus on how to support nonexperts in exploring and comparing their own personal genomic report with those of other people. We designed and evaluated CrossGenomics, a novel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…A project, GenomiX Genome Exploration, was created in Open Humans that invited Members who had publicly shared their genetic data in Open Humans to engage with a custom visualization derived from their existing public data and associated interpretations. The study found various design implications in genome data engagement, including the value of affording users the flexibility to examine the same report using multiple views [83].…”
Section: Resultsmentioning
confidence: 99%
“…A project, GenomiX Genome Exploration, was created in Open Humans that invited Members who had publicly shared their genetic data in Open Humans to engage with a custom visualization derived from their existing public data and associated interpretations. The study found various design implications in genome data engagement, including the value of affording users the flexibility to examine the same report using multiple views [83].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have documented that healthcare providers find genomic reports difficult to read and use [27][28][29][30][31] , which may be due to lack of expertise in genomics, to reports crafted without good usability principles or both. To date, there are few papers focused on the usability of genomic reports [33][34][35][36] . Patient groups are interested in standardization and usability of their medical data, and the Association of Molecular Pathology and other professional societies are involved in these efforts (Common Cancer Testing Terminology, https://www.commoncancertestingterms.org, last accessed 4/6/2021).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A project, GenomiX Genome Exploration, was created in Open Humans that invited members who had publicly shared their genetic data in Open Humans to engage with a custom visualization derived from their existing public data and associated interpretations. The study found various design implications in genome data engagement, including the value of af-fording users the exibility to examine the same report using multiple views [80].…”
Section: Data Re-use In Genetic Data Visualization Researchmentioning
confidence: 99%